Swami Dayanand and his influence in Arousing Nationalism amongst the Women of Rajasthan and Punjab (with special reference to the role of Arya Kanya Mahavidhyalaya) - Dr. Meghna Sharma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Reen Court in his book ’The Soul of India’ remarks that ’’there is no doubt whatsoever that the 1905 Revolt of Bengal was an indirect result of the Arya Samaj’s nationalism and Dayanand’s organization was indeed the first focal point of Indian Nationalism’’. It is strange that Sarla Devi did so much for the British but she was also kept under surveillance and her husband Ram Bhaj Dutt was arrested. It was largely for their connection with the Arya Samaj. The peasant’s movements of Rajasthan contributed a lot in creating an atmosphere of political awareness among the natives of Rajasthan and there is no doubt in saying that the general masses became aware for initiating such movements only by the inspiration of Arya Samaj. The founders of Kanya Mahavidhyalaya (KMV), Jullunder, Punjab consistently refused to ally it with the government school system even though this meant losing the government grant and making do with its own severely limited resources. This ensured that KMV enjoyed much greater freedom and opportunity for innovation. Interesting also is the gradual transition from the older role of women as supportive homemakers to the newer one of women as participants in the struggle. Several stories idealise the wife, mother or sister who keeps the home fires burning while the male fights heroically or languishes in prison. The woman is shown as willingly sacrificing her loved one for the country. This paper brings forward the story how women were inspired by Swami Dayanand and the activities of Arya Samaj in raising the cause of nationalism thus showcasing their political participation in contemporary scenario.